Early outcomes of transcatheter tricuspid valve-in-valve implantation: a case series. (25th January 2019) - Viotto, Guilherme; Paim, Leonardo; Souza, Renato; Aprígio, Joaquim; Lacerda, Lucas; Pomerantzeff, Pablo; Jatene, Marcelo B; Palma, José Honório; Jatene, Fabio B
Abstract: OBJECTIVES: In this study, we sought to evaluate early outcomes of transcatheter valve-in-valve implantation in patients with a degenerated bioprosthesis in the tricuspid position. METHODS: We used a prospective study, which included patients with a degenerated bioprosthesis in the tricuspid position who were considered high-risk by our heart team and who underwent a valve-in-valve implantation. The procedures were performed via transjugular venous access and were done with the patient under general anaesthesia with transoesophageal echocardiographic and fluoroscopic guidance. Perioperative data were analysed, and the patients were followed prospectively. RESULTS: Seven patients were included. The baseline diagnoses were 3 patients with Ebstein's anomaly, 1 patient with tetralogy of Fallot, 1 patient with neonatal endocarditis, 1 patient with ventricular septal defect with a double tricuspid lesion and 1 patient with rheumatic mitral and tricuspid valve who underwent a combined transapical mitral and transjugular tricuspid valve-in-valve implantation. The mean age was 33 ± 10.8 years and 57.1% of the patients were men. The mean number of previous thoracotomies was 3 ± 2 (range 1–5) procedures. The mean follow-up was 1.24 years. The implant was successful in all cases, and there was no need for conversion to open surgery. There were no deaths during the study period, and all patients are currently in the New York Heart Association functional class I/II. There was a statistically significant difference when the mean transvalvular gradients preimplantation and postimplantation were compared ( P < 0.001). CONCLUSIONS: Percutaneous tricuspid valve implantation should be considered a safe and effective therapy and stands as a viable, reliable alternative for the treatment of a degenerated bioprosthesis in high-surgical-risk/inoperable patients.